Identificationof resistance sources to banded leaf and sheath blight (Rhizoctonia solani f. sp. sasakil) in maize - S.C. SAXENA; S.V.S. CHAUHAN, ANSHU GARG, B.M. PRASANNA*, R.C. SHARMA, R.S. RATHORE (Indian Phytopathology, 2007)
The Banded leaf and sheath blight (BlSB) disease, incited by Rhizoctonia solani f. sp. sasakii, causes considerable damage to maize (Zea mays L.) worldwide, particularly in the tropical Asia. Evaluation of a set of 29 tropical maize inbred lines in replicated trials under artificial inoculation in field conditions at Udaipur (Rajasthan,Western India), Pantnagar (Uttarakhand, North-Eastern India), and New Delhi (North India) during three consecutive years (2002-2004).While many of the Indian and CIMMYT (International Maize and Wheat Improvement Center, Mexico) inbred lines displayed susceptibility to BlSB, CA00106 was the only inbred that revealed moderate resistance to the three BlSB isolates. CM104 was moderately resistant at Udaipur and Pantnagar, but was susceptible at Delhi. CM10Swas moderately resistant at Pantnagar and susceptible at both Udaipur and Delhi. Among the CIMMYT inbred lines, CA00310 revealed moderate resistance at Udaipur and Delhi, while CA00344 and CA00370 were moderately resistant at Pantnagar and Delhi.The study highlights differential responses of the same set of maize genotypes to BlSB isolates at the three ’hot spots’ in India, with significant genotype x environment interactions.